Pedogenic Forms of Iron in Soils Developed from Four Parent Materials - Ayodele Owonubi (UNIVERSITY OF LAMPUNG, 2020)
Information on the distribution of various forms of iron in soils are valuable in the study of soil genesis. The objective of this study was to to evaluate the pedogenic forms of iron in soils developed over basement complex and basaltic parent materials of the study area. Geologic units considered in the basement complex area were granite gneiss, biotite granite and migmatite. Stratified random sampling formed the basis for field work. Soil sampling was carried out by digging at least two soil profile pits in each geologic unit. Organically bound, amourphous and total iron oxides were estimated using 0.1 M sodium pyrophosphate, acidified (pH 3) ammonium oxalate, and dithionite-citrate-bicarbonate method, respectively. The total Fe in the soil samples were determined after a mixed acid digestion. In general, total iron fractions were statistically similar among the soils of basement complex geologic units but significantly lower than those of soils derived from basaltic rocks. However, the distribution of iron oxide fractions was similar among the basement and basaltic geologic units. Furthermore, there were significant differences in the distribution of iron oxides in the B horizons of basement complex derived soils. Consequently, the quantity of iron oxides in the B horizon was in the order migmatite > biotite granite > granite gneiss. About 70% of total iron oxides in the soils over granite gneiss, biotite granite and basaltic rocks was amorphous in nature. Furthermore, total iron oxides constitute less than 20% of total clay both in the basement complex and basaltic soils.